The clinical outcome of minor changes in serum creatinine for patients after curative gastrectomy: a prospective study - Cai, Wen-Tao; Zeng, Xiu-Ya; Huang, Yun-Shi; Chen, Wei-Sheng; Chen, Xiang-Jian; Xie, Xian-Hai (Frontiers in Oncology, 2024)
Introduction Patients with renal insufficiency are more prone to postoperative complications (PCs). Studies have shown that minor changes in serum creatinine (SCr), immediately post-surgery, can aid in assessing patients’ renal function. This study aimed to explore the relationship between the changes in SCr and PCs in patients with gastric cancer (GC). Materials and methods We prospectively collected data regarding the SCr of 530 GC patients, within 2 weeks before surgery and within 24 hours after surgery in our hospital (2014–2016). The patients were divided into three groups according to the level of SCr change after surgery: reduced (<10%), normal (10%), and elevated (>10%) creatinine groups. Univariate and multivariate logistic analysis were performed to evaluate its correlation with short-term PCs in the patients. The R language was used to construct a nomogram. Results 83, 217, and 230 patients were assigned to the elevated, reduced, and normal SCr groups, respectively. Multivariate analysis showed that the reduced and elevated SCr groups were independently associated with the occurrence of PCs and severe postoperative complications (SPCs), respectively. Additionally, postsurgical SCr change, age, hypoalbuminemia, total gastrectomy, combined resection, and laparoscopy, were independently related to PCs. Combining the above influential factors, the predictive model can distinguish patients with PCs more reliably (c-index is 0.715). Conclusion Post-surgery, reduced SCr is a protective factor for PCs, while elevated serum creatinine is an independent risk factor for SPCs. Our nomogram can identify GC patients with high risks of PCs.